2018
DOI: 10.1038/s41598-018-28528-1
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and exosomal miRNA editing in Non-Small Cell Lung Cancer

Abstract: RNA editing in microRNAs has been recently proposed as a novel biomarker in cancer. Here, we investigated RNA editing by leveraging small-RNA sequencing data from 87 NSCLC (Non-Small Cell Lung Cancer) samples paired with normal lung tissues from The Cancer Genome Atlas (TCGA) combined with 26 plasma-derived exosome samples from an independent cohort. Using both the editing levels and microRNA editing expression, we detected deregulated microRNA editing events between NSCLC tumor and normal tissues. Interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 42 publications
5
43
0
Order By: Relevance
“…In consistent with our research, Soundararajan et al identi ed 652 editing events in lung cancer, which were located in the 3´UTR of 205 target genes and mapped to 932 potential microRNA target binding sites [92]. All together these ndings are inconsistent with Liang [96]. Indeed, our results showed miR-34a, a cancer-speci c edited microRNA, was edited in 10 position.…”
Section: Discussionsupporting
confidence: 85%
“…In consistent with our research, Soundararajan et al identi ed 652 editing events in lung cancer, which were located in the 3´UTR of 205 target genes and mapped to 932 potential microRNA target binding sites [92]. All together these ndings are inconsistent with Liang [96]. Indeed, our results showed miR-34a, a cancer-speci c edited microRNA, was edited in 10 position.…”
Section: Discussionsupporting
confidence: 85%
“…All the six edited sites have preferable sequence motifs for ADAR enzymes, which is (1) over-represented uridine (U) but depleted guanosine (G) at the nucleotides before the edited sites and (2) over-represented guanosine at the nucleotides after the edited sites. Confidence of edited site (Li et al, 2018) reported in brain (Alon et al, 2012) and reported in exosomes (Nigita et al, 2018).…”
Section: Select A-to-i Editing In Exosome-enriched Fraction Mirnasmentioning
confidence: 54%
“…All the edited sites have been reported as "confident" in a recent comprehensive analysis profiling ADAR editing (Li et al, 2018). In addition, three of them (miR-411-5p at position 5, miR-376b-3p at position 6, and miR-421-3p at position 14) have been reported in brain (Alon et al, 2012), with comparable editing levels, while miR-411-5p (at position 5) has been reported in plasma-derived exosomes (Nigita et al, 2018). Moreover, they all have preferable sequence motifs for ADARs, which is uridine (U) enriched and guanosine (G) depleted at the nucleotide preceding the edited sites (four U and zero G out of six) and guanosine enriched at the nucleotides following the edited sites (five out of six) (Figure 8).…”
Section: Select A-to-i Editing In Exosome-enriched Fraction Mirnasmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition to expression level analysis, variation in sequences, such as RNA editing, can also be detected by the RNA-seq method. Very recently, Nigita et al found that miRNA editing events also occur in blood circulation, and the analysis of exosomal edited cargo was able to distinguish between normal and tumor sample subtypes [66]. In MDS, a pilot study on RNA editing was published by Crews et al, who showed that A-to-I RNA editing rates were increased in AML-MRC compared to MDS progenitors and that the differential expression of certain sites was as high as 70% [67].…”
Section: Discussionmentioning
confidence: 99%